Oral analgesic 24 hours after major operation: a comparative study of oral celecoxib and tramadol in patients undergoing major gynaecological operation - Mohamed, Rozilah @ Abdul Hadi; Abdullah, Nor Zamzila; Md Ralib, Azrina; Abd. Wahab, Noraziana; Mat Nor, Mohd Basri (Confederation of the ASEAN Societies of Anaesthesiology (CASA), 2007)
Adequacy of postoperative pain control is one of the most important factors in determining when a patient can be safely discharged from a surgical facility. Furthermore it has a major influence on the patient's ability to resume the normal activity of daily living. Tramadol is a weak opioid analgesic that acts mainly on µ-opioid receptor and has been proven to provide effective and safe analgesic to post operative patients.Celecoxib(celebrex) is a highly selective COX-2 inhibitor. It belongs to nonsteroidal anti-inflammatory drugs (NSAIDs) group which reduces inflammation and pain while minimizing gastrointestinal adverse reaction. This selectivity feature makes celecoxib an attractive alternative to opioids for the control of postoperative pain. The purpose of this study was to evaluate the effectiveness of oral celecoxib, in comparison with oral tramadol, in term of analgesic properties and the need for additional tablet acetaminophen as rescue pain reliever in patients undergoing elective gynaecological operation. A randomized, single-blinded study was conducted on 100 ASA I and II patients who were randomized into two groups;tramadol or celecoxib. Following major gynaecological surgery, all patients were given standard patient-controlled analgesia(PCA) regime with intravenous morphine. Patients either received oral tramadol 100 mg 8 hourly or oral celecoxib 200 mg. 12 hours for analgesia 24 hours post operation. Tablet acetaminophen was available as a rescue analgesic. Patients were monitored for pain according to Modified Pain Score, haemodynamic changes and side effects. They were evaluated at 24, 32, 40 and 48 hours post operation. The mean pain score at 24,32,40 and 48 hours post operation were 0.86 ± 0.45,± 0.65 ± 0.47, 0.42 ± 0.50 and 0.14 ± 0.35 in celecoxib and group and 0.92 ± 0.44, 0.78 ± 0.41,0.46 ± 0.54 and 0.18 ± 0.39 in tramadol group respectively. There were no significant differences in the mean pain score and between the two group at each point of assessment (p>0.05). None of the patients requested for tablet acetaminophen. Patient satisfaction was similar in both study groups. This study indicates that oral celecoxib 200mg 12 hourly is adequate and suitable to be used as an alternative to oral tramadol 100mg 8 hourly in controlling pain 24 hours following major operation without the need for additional tablet acetaminophen.